Limited efficacy of a therapeutic anti-CD40 monoclonal antibody to inhibit activated CD4 T cell autoimmunity in vitro - Chelsea Gootjes; Jaap Jan Zwaginga; Tatjana Nikolic; Bart O. Roep (PLoS ONE, 2026)
Iscalimab is a nondepleting anti-CD40 monoclonal antibody, expected to suppress immune responses by blocking the costimulation by antigen-presenting cells through CD40-CD40L ligation. This therapeutic antibody indeed inhibited proliferation of B lymphocytes and TNF production by dendritic cells and is being tested in clinical trials to treat B cell mediated autoimmune diseases. Since iscalimab showed limited clinical benefit and did not improve kidney and liver transplantation outcomes compared to standard tacrolimus treatment, we studied whether a biosimilar of iscalimab affects T cell responses in vitro. For this, we stimulated autoreactive effector and alloreactive naïve CD4 T cells in the presence of anti-CD40 antibody and measured the impact on cell proliferation. While we confirmed the capacity of iscalimab biosimilar antibody to bind to B cells and dendritic cells and to completely inhibit proliferating B cells, it showed limited to no efficacy to inhibit proliferation of diabetogenic beta-cell specific effector CD4 T cell clones. The CD40 blockade also did not affect the induction of proliferation of naïve alloreactive CD4 T cells, by dendritic cells. Based on our in vitro data pointing to minimal inhibition of T cells by CD40 blockade, we propose that iscalimab may not suffice to accomplish durable benefit as intervention strategy to treat type 1 diabetes or other T cell mediated diseases.